THE EFFECT OF EXTRACURRICULAR SCOUTING ACTIVITIES AND STUDENT DISCIPLINE ON THE LEARNING OUTCOMES - Mohamad Alwi Pomou; Rosman Ilato; Sudirman Sudirman; Abdulrahim Maruwae (Jambura Economic Education Journal, 2023)
This research aims to determine the effect of scout extracurriculars and student discipline on student learning outcomes in economics subject in grade XI of Social Science at SMA Negeri 2 Limboto, Gorontalo Regency. This quantitative research involves 38 samples, and the data are collected through a questionnaire with multiple linear regression analysis techniques. The results indicate that partially or simultaneously, the variables of scout extracurricular and student discipline affect student learning outcomes in economics subject in XI grae of social science at SMA Negeri 2 Limboto, Gorontalo Regency positively and significantly. The results are obtained through the coefficient of determination (R2) of 85.70% of the variable scout extracurricular and student discipline on student learning outcomes in economics subject in grade XI of Social Science at SMA Negeri 2 Limboto, Gorontalo Regency. Meanwhile, the other 14.30% is influenced by other variables not explained in this research. .